Pengaruh Kegiatan Industri terhadap Kondisi Sosial Ekonomi Masyarakat di Kecamatan Cibogo Kabupaten Subang - Muhammad Luthfi Abdul Wahid; Chusharini Chamid (UNISBA Press, 2022)
Abstract. Based on the Regional Regulation of Subang Regency Number 3 of 2014 concerning Spatial Planning for the RTRW of Subang Regency in 2011-2031, it explains that Cibogo District is one of the industrial designation areas (KPI) in Subang Regency, this study aims to determine the influence of industry on the socio-economic conditions of the community by industrial activities in Cibogo District. The object of research is all people who live in Cibogo sub-district with the criteria men and women of productive age and working in industry or being affected by industrial activities. The method used is multiple linear regression . Based on the results of F test, significance value for the influence of the existence of industry (Y) on the socio-economic conditions of the community (X) is 0.014 < 0.050 and f count 6.242 > f table 3.94 then reject Ho accept Ha means that there is an influence of the existence of industry (X) on the socio - economic condition of the community ( Y ) is significant . Based on the table of T test results, significance value for the influence of the existence of industry (Y) on the socio-economic conditions of society (X) is 0.014 < 0.050, and T count is 2,498 > T table 1,984 then reject Ho accept Ha which means there is an influence of the existence of industry ( X ) on the socio - economic conditions of the community ( Y ) significantly . Abstrak. Berdasarkan Perda Kabupaten Subang Nomor 3 Tahun 2014 Tentang Rencana Tata Ruang Wilayah RTRW Kabupaten Subang tahun 2011 – 2031 menjelaskan Kecamatan Cibogo menjadi salah satu kawasan peruntukan industry ( KPI ) di Kabupaten Subang, penelitian ini bertujuan untuk mengetahui pengaruh industry terhadap kondisi sosial ekonomi masyarakat dengan adanya kegiatan industry di Kecamatan Cibogo . Objek penelitian yaitu seluruh masyarakat asli yang tinggal di kecamatan cibogo dengan kriteria laki-laki dan perempuan usia produktif dan bekerja di industri atau terdampak oleh adanya kegiatan industri . Metode yang digunakan yaitu regresi linier berganda . Berdasarkan hasil uji F dapat diketahui nilai signifkansi untuk pengaruh keberadaan industry ( Y ) terhadap kondisi social ekonomi masyarakat ( X ) adalah sebesar 0.014 < 0.050 dan f hitung 6.242 > f tabel 3.94 maka tolak Ho terima Ha artinya terdapat pengaruh keberadaan industry ( X ) terhadap kondisi sosial ekonomi masyarakat ( Y ) secara signifkan . Berdasarkan tabel hasil uji T dapat diketahui nilai signifkansi untuk pengaruh keberadaan industry ( Y ) terhadap kondisi social ekonomi masyarakat ( X ) adalah sebesar 0.014 < 0.050 , dan T hitung 2.498 > T tabel 1.984 maka tolak Ho terima Ha yang artinya terdapat pengaruh keberadaan industry ( X ) terhadap kondisi social ekonomi masyarakat ( Y ) secara signifkan .